Pelatihan dan Pendampingan Pencatatan Laporan Keuangan Menggunakan Aplikasi Sepran pada Pelaku Usaha UMKM Batik Tulis Safira di Pakandangan Barat - Hertin Khalifatun Nisa Arifah; Jannatul Firdaus; Any Sani’atin; Ediawan Ediawan; Hanifah Fauziyah; Nurul Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
Financial statements are a regularly arranged collection of data that shows a company's financial position at a specific point in time. One of the challenges is the limited knowledge about preparing financial statements using digital finance applications. The primary objective of this community service activity is to train and disseminate information about the importance of digital financial reporting. The research aims to educate Safira batik SMEs about digital financial statements. Socialization and training methods were used in this study. The findings showed that before the training, only 20% were aware of financial statements but did not know about digital financial statements; however, after the training, their knowledge increased by 80%. Before the training, 10% only knew how to record financial statements but had not recorded financial statements using a digital finance application; however, after the training, their knowledge increased by 90%.